Kompetensi kepimpinan pendidikan sekolah rendah dalam bidang Pengurusan Strategik - Redzuan, Ahmad (2010)
This research is conducted to study the educational competency at primary school level which is focusing toward headmaster's management strategic in Perlis from other teacher's point of view. 10 primary schools are selected in which respondents are involved in this research. Leadership competency and strategically management is measured by using Leadership Competency Questionnaire: Manager and Team Members which is designed by Pollack Learning Alliance and Leadership Management Group: Building Excellence at all level. To collect all the information and data questionnaire instrument has been used. Descriptively, the data collected are analyses by using Statistical Package for Social Science (SPSS) software version 12.0 in order to get min, mod and percentage as well as inference in form of t-test, ANOVA and correlation. From the result, it shows that there is significant disparity at leadership management competency in education at primary school in term of demographic. The result also shows that there is significant relationship between leadership management competency at primary school and strategically management practice. Researcher hopes that primary school management especially the headmaster should be competent in leadership and strategically management in all administrative work. Thus, leadership education must uphold the personality and huge knowledge, especially in the aspect of leadership culture and effective management, with high quality and excellence which is to motivate and mould their professionalism. Good quality of leadership and management will be more effective, especially in the process of decision making in a very complex environment and also all the present and future challenges